Gangsterism Behaviour and Culture: A Threat to Investment Climate and Economic Security in Industrial Zones - Siahaan, Junior Ternama; Halomoan FS Alexandra; Parluhutan Sagala (International journal of technology and education research, 2025)
The proliferation of gangsterism in Indonesia’s industrial zones has emerged as a serious threat to the investment climate and national economic stability. Informal violence, extortion of logistics, and the monopolisation of distribution channels by mass organisations operating under gangsterism create legal uncertainty, reduce business efficiency, and generate hidden economic costs that negatively affect investor confidence. This study aims to systematically explore the behavioural and cultural characteristics of gangsterism in industrial areas and to examine the social, legal, and economic factors driving its expansion. Employing a descriptive qualitative approach, the research draws on secondary data from academic journals, institutional reports, and legal documents. The findings reveal that gangsterism is not merely a consequence of weak law enforcement but also a product of social inequality, structural unemployment, and the involvement of local political actors in informal power relations. The study further shows that gangsterism disguised as community organisations follows a systematic pattern with the potential to disrupt industrial supply chains and undermine long-term investment certainty. Its original contribution lies in the identification of two forms of industrial gangsterism—informal and formal-political and in mapping their nexus with the degradation of microeconomic security. The study recommends the establishment of an Anti-Gangsterism Task Force in strategic industrial areas as well as the strengthening of regulations and inter-agency coordination to foster a clean, stable, and globally competitive industrial ecosystem.